Analisis Gereja dalam Perjanjian Lama dan Gereja dalam Perjanjian Baru : Kajian Eklesiologi - Yuslina Halawa; Abad Jaya Zega (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This research aims to analyze how the church in the old and new testaments. The approach used in this research is descriptive qualitative, which aims to understand the structure so that it has a major influence on contemporary Christianity. From a conceptual perspective, the Church in the Old Testament is understood as a community of God's chosen people whose identity is attached to the ethnic unity of the Israelites and attachment to the law within the framework of the covenant. While in the New Testament, the understanding of the Church undergoes a transformation into a universal, inclusive, and spiritual community of faith, consisting of all people who believe in Jesus Christ as Lord and Savior, without ethnic or legal restrictions. In terms of structure and leadership, the Old Testament features a leadership system based on heredity and institutional positions such as priests and prophets who mediate the people's relationship with God; whereas in the New Testament, leadership is no longer hereditary, but based on the gift of the Holy Spirit, with a collegial, functional and participatory service model and Christ as the Head of the Church, emphasizing the dimensions of relationships and service in the community.In terms of sacraments, religious practices in the Old Testament such as religious celebrations functioned as symbols of obedience and identity of the people's covenant with God, but in the New Testament, so the sacramental meaning is renewed through baptism and holy communion which are spiritual and Christocentric, marking new fellowship in Christ in the context of grace. This study concludes that the New Testament cannot be understood as a break with or an abolition of the traditions and practices that existed in the Old Testament. Instead, the New Testament represents a theological fulfillment and essential transformation of the entire narrative and system that had been built in the Old Testament.